2011
DOI: 10.1038/ijir.2011.10
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the relationship between coronary artery ectasia and erectile function score

Abstract: The relation between coronary artery ectasia (CAE) and erectile dysfunction (ED) has not been studied so far. Hence, we decided to investigate the erectile function score in patients with CAE. We investigated the international index of erectile function (IIEF)-5 score in 34 men with CAE, 38 men with coronary artery disease (CAD), and 30 male controls with normal coronary arteries whose mean ages were 53.2 ± 5.6, 51.4 ± 7.8, and 49.6 ± 8.6 years, respectively. Erectile function was evaluated by the five-item ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
(39 reference statements)
0
4
0
Order By: Relevance
“…In one study by Akcay et al, 24 it was found that IIEF scores were significantly lower in the group with coronary artery ectasia (CAE) and CAD than in control groups with normal coronary arteries. This study suggests that ED and CAE may be different manifestations of a common underlying vascular pathology and ED is frequently seen in CAE at least as much as in CAD.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In one study by Akcay et al, 24 it was found that IIEF scores were significantly lower in the group with coronary artery ectasia (CAE) and CAD than in control groups with normal coronary arteries. This study suggests that ED and CAE may be different manifestations of a common underlying vascular pathology and ED is frequently seen in CAE at least as much as in CAD.…”
Section: Discussionmentioning
confidence: 98%
“…Each question was scored from 1-5 with a maximum score of 25 denoting healthy subjects. ED was classified into five severity levels, ranging from none (22)(23)(24)(25) to severe (5-7). 6 Statistical analysis Continuous variables were given as mean ± s.d.…”
Section: Erectile Function Assessmentmentioning
confidence: 99%
“…18 Specifically, recent attention has been focused on arterial atherosclerosis as one of the important risk factors BPE, benign prostatic enlargement; IPSS, International Prostate Symptom Score; LUTS, lower urinary tract symptoms; PMR, postmictional residual urine volume; PV, prostate volume; Qmax, maximum mean peak urinary flow rate; other abbreviations as in Table 1. Variables were given as mean AE standard deviation.…”
Section: Commentmentioning
confidence: 99%
“…This was thought to be related to coronary endothelial dysfunction, assessed by plasma asymmetric dimethyl arginine (ADMA) levels and endothelium-dependent flow-mediated dilatation (FMD), having excluded the inflammatory response as a potential contributor (31). Ackay et al (32) found a direct relationship between CAE and erectile dysfunction suggesting that endothelial dysfunction in CAE may manifest in two different forms, thus adding to the already existing pathophysiological confusion.…”
Section: Cae Slow Coronary Flow and Endothelial Dysfunctionmentioning
confidence: 99%